Pengaruh Suhu Dan Waktu Proses Karboksimetilasi Terhadap Karakteristik Carboxymethyl Cellulose (CMC) dari Onggok Singkong - Sutha, K.G. Govardhana; Arnata, I Wayan; Ganda Putra, I Gusti Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
Onggok is an organic waste from tapioca production rich in cellulose but has not been utilized fully for other usages. This study aimed to determine the appropriate temperature and time for the carboxylation process to produce CMC from cassava with the best characteristics. This study used a factorial randomized block design. Factor 1 was temperature (40oC, 55oC, 70oC) and factor 2 was time (2 hours, 3.5 hours, 5 hours). The observed variable was yield, water content, substitution degree, viscosity, and purity. The results showed that the interaction temperature and time affected the yield, water content, degree of substitution, viscosity, NaCl content, and purity of CMC. The best treatment was obtained from a combination of 40oC temperature treatment with a processed time of 5 hours with the yield value, moisture content, degree of substitution, viscosity, and purity of CMC 83.97±1.36%, 9.58±0.67%, 0,89±0.06, 105.00±21.21cPs, and 97.55±0.66%, respectively